TARI BARIS JOJOR PADA PIODALAN PURA BALE AGUNG DESA PAKRAMAN SEKARDADI: RITUAL, MAKNA, DAN PENDIDIKAN KEBERAGAMAAN - Sutamayasa, I Wayan; Redana, I Made; Mahardika, I Gusti Ngurah Agung Wijaya (UHN IGB Sugriwa Denpasar, 2025)
This study aims to examine the form, function, meaning, and religious educational values of the Baris Jojor Dance performance during the piodalan ceremony at Pura Bale Agung, Desa Pakraman Sekardadi, Kintamani District, Bangli Regency. The research employed a descriptive qualitative method with a religious approach oriented toward phenomenological, theological, and socio-humanistic understanding. Data were collected through observation, interviews, and documentation, and analyzed using descriptive qualitative techniques. The findings reveal that the Baris Jojor Dance is a sacred performance (seni wali) traditionally presented in the Dewa Yajña ritual, performed by eight male dancers carrying long spears as symbols of warrior virtues. The functions of Baris Jojor encompass religious dimensions as sacred offerings, social functions as community solidarity, educational roles in character formation, and cultural significance as a medium of heritage transmission. Its meanings reflect the triumph of dharma over adharma, cosmic harmony, and spiritual communication between humans and the divine. The religious educational values embedded include tattwa (philosophy), susila (ethics), and upakara (ritual practice), along with cultural inheritance for younger generations. Thus, the Baris Jojor Dance contributes significantly to strengthening spirituality, morality, and cultural identity within Balinese Hindu society.